2018
DOI: 10.1038/s41598-018-36316-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing and transcriptome analysis to identify genes related to biosynthesis of aristolochic acid in Asarum heterotropoides

Abstract: Asarum spp. are important medicinal plants that have the potential for use in treating various types of fevers. Aristolochic acid is one of the main toxic compounds present in these plants. To improve our understanding of the biosynthetic pathway of aristolochic acid, we sequenced the transcriptome of the root and leaf tissues of Asarum heterotropoides and performed de novo sequence assembly. The data were stitched together to produce 468,357 transcripts with an N50 of 611 bp. The data were annotated with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…AAs are biogenetically derived from BIA precursors, and magnoflorine is always identified together with AAs in various Aristolochia species [ 11 ]. In addition, norlaudanosoline has been considered to be an intermediate of AA biosynthetic pathways for several decades [ 10 14 ]. However, the distribution of norlaudanosoline in plants is narrow: it has only been found in M. cordata [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AAs are biogenetically derived from BIA precursors, and magnoflorine is always identified together with AAs in various Aristolochia species [ 11 ]. In addition, norlaudanosoline has been considered to be an intermediate of AA biosynthetic pathways for several decades [ 10 14 ]. However, the distribution of norlaudanosoline in plants is narrow: it has only been found in M. cordata [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, there is little information available on this pathway, which was analyzed only in a few studies in the 1960s [ 10 13 ]. In addition, only one gene (TyrDC) that is probably involved upstream of the pathway has been cloned [ 14 ]. In the AA biosynthetic pathway proposed in the 1960s, norlaudanosoline, orientaline, orientalinone, and orientalinol were considered to be intermediates of AA biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Among these unigenes, 102,154 (75.13%) were mapped to seven public databases. Compared with other medicinal plant transcriptome databases, the average length and N50 values of unigenes in C. chinense (average length = 1195 bp; N50 = 1890 bp) were longer than those in Artemisia argyi (average length = 926 bp; N50 = 1456 bp) [17], Oroxylum indicum (average length = 1080 bp; N50 = 1783 bp) [21], and Asarum heterotropoides (average length = 611 bp; N50 = 507.36 bp) [22]; these results demonstrated that our transcriptome database was of high quality. In particular, the sequence size distribution was homogeneous and 10,942 (48.61%) unigenes were longer than 1000 bp, indicating successful generation of transcriptional data.…”
Section: Discussionmentioning
confidence: 99%
“…AAs exhibit nephrotoxicity, liver toxicity, carcinogenesis, and mutagenesis and are classified as grade I carcinogens (Wang et al, 2018). Further studies indicate that AAs have multiple types of molecular structure, with aristolochic acid I (AAI) being the most toxic (Balachandran et al, 2005; Supplementary Figure S2).…”
Section: Introductionmentioning
confidence: 99%